Penerapan Model Problem Based Learning Berbantuan Media Mobile Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Muhammad, Muhammad; Aji, Waskito; Anwar, M Syaiful (Faculty of Teacher Training and Education of Undaris, 2025)
This research aims to improve critical thinking skills of elementary school students using Problem Based Learning model assisted by Mobile Learning media. The type of research used is quasi-experimental with a nonequivalent control group design. The population of this research were V grade students on Ungaran Barat in the 2024/2025 academic year. Sample of this research was V grade students of SDI Istiqomah. The sampling technique used in this study was Purposive Sampling. The data collection technique in this study used a test technique in the form of multiple choice and descriptive questions, as well as a non-test technique using observation and documentation. Data were analyzed using the gain score test and t-test. The results showed that there was a significant increase in students' critical thinking skills using the PBL model assisted by mobile learning media. There was a significant difference in the average score of critical thinking skills between the experimental class and the control class with a significance level of 5% with an N-Gain of the experimental class of 0.72 and the control class of 0.43. The results of the independent test stated that there was a difference between the experimental class and the control class, indicated by the t-value of 0.472 with a significance level of 0.000. This shows that the PBL model assisted by mobile learning media can improve students' critical thinking skills.Keywords: Problem Based Learning, Mobile Learning, Critical Thinking Skills